The Inhibitory Activities and Antiviral Mechanism of Medicinal Plant Ingredient Quercetin Against Grouper Iridovirus Infection - Liu, Mingzhu; Yu, Qing; Xiao, Hehe; Li, Mengmeng; Huang, Yaming; Zhang, Qin; Li, Pengfei (Frontiers in Microbiology, 2020)
Singapore grouper iridovirus (SGIV) causes high mortality rates in mariculture, and effective treatments against SGIV infection are urgently required. Illicium verum Hook. f. (I. verum) is a well-known medicinal plant with a variety of biological activities. The natural ingredient quercetin isolated from I. verum could effectively inhibit SGIV infection in a dose-dependent manner. The possible antiviral mechanism of quercetin was further analyzed in this study. It showed that quercetin did obvious damages to SGIV particles. Furthermore, quercetin could interfere with SGIV binding to targets on host cells (by 76.14%), disturb SGIV invading into host cells (by 56.03%), and effect SGIV replication in host cells (by 52.73%), respectively. Quercetin had the best antiviral effects during the SGIV life cycle of binding to the receptors on host cells' membranes. Overall, the results suggest that quercetin has direct and host-mediated antiviral effects against SGIV and holds great potential for developing effective drugs to control SGIV infection in aquaculture.